2019
DOI: 10.1111/1365-2435.13416
|View full text |Cite
|
Sign up to set email alerts
|

The correlated evolution of social competence and social cognition

Abstract: Knowing which of correlated traits are more strongly targeted by selection is crucial to understand the evolutionary process. For example, it could help in understanding how behavioural and cognitive adaptations to social living have evolved. Social competence is the ability of animals to optimize their social behaviours according to the demands of their social environment. It is a behavioural performance trait that expresses how well a whole organism performs complex social tasks, such as choosing mates, rais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 65 publications
(179 reference statements)
1
35
0
Order By: Relevance
“…forebrain size, cerebellum size, and cerebellum cell density) in predicting performance in the previous analyses. With the new analyses, we tested predictions for social competence instead 42 , 43 , 55 . Here, we found that individuals making optimal strategies, that is, having social competence, had relatively larger forebrains than those adopting not-optimal strategies (GLM: X 2 = 6.118, p = 0.013, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…forebrain size, cerebellum size, and cerebellum cell density) in predicting performance in the previous analyses. With the new analyses, we tested predictions for social competence instead 42 , 43 , 55 . Here, we found that individuals making optimal strategies, that is, having social competence, had relatively larger forebrains than those adopting not-optimal strategies (GLM: X 2 = 6.118, p = 0.013, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our study showed that linking social complexity, brain features and cognitive performance in wild animals is rather complex. By incorporating information about the ecology of cleaning interactions as a function of cleaner fish densities, the concept of social competence emerged as a suitable framework to link forebrain size to cognitive performance (see review by Varela et al 55 ). As it stands, ecological conditions can determine what decision-rules are locally adaptive and apparently a larger forebrain facilitates the acquisition of these rules.…”
Section: Discussionmentioning
confidence: 99%
“…The perspective of social competence (Taborsky and Oliveira 2012;Bshary and Oliveira 2015;Fernald 2017;Varela et al 2020) is relevant for these winner and loser effects. A key idea is that individuals adjust their fighting behaviour based on the consequences of winning or losing an interaction, using information obtained through learning.…”
Section: Discussionmentioning
confidence: 99%
“…To respond appropriately to the environment may pose a cognitively demanding challenge particularly with regard to the social environment of an individual, due to the inherent dynamics and involved conflicts of interest (Varela, Teles, & Oliveira, ; Weitekamp & Hofmann, ). The first difficulties for desiring receivers of social cues and signals regard perception, detection and recognition of relevant signals.…”
Section: The Costs Of Processing Storing and Retrieving Informationmentioning
confidence: 99%
“…In their article, Susana Varela, Magda Teles and Rui Oliveira (Varela, Teles, & Oliveira, ) draw a firm line between social cognition and social competence, the former being viewed as a by‐product of natural selection on the latter. Their conceptual framework highlights that selection directly acts on functional performance traits such as choosing mates, raising offspring and forming social bonds, while lower ranking traits such as social and non‐social cognition constitute correlated, secondary targets of selection.…”
Section: Evolutionary Ecology Of Social Decisions In the Light Of Senmentioning
confidence: 99%